Probability of success in the search for a related bone marrow donor in Cologne, Germany using HLA‐A, ‐B and ‐DRB1 haplotype frequencies. (21st September 2018) - Hellmann, Daniel M.; Radojska, Stela; Fimmers, Rolf; Gathof, Birgit S.
Abstract : Between 2004 and 2013, 603 patients and their relatives ( n  = 1297) were typed as part of the search for a suitable HLA‐matched donor in their nuclear and extended families at the central service provider for transfusion medicine at the University Hospital of Cologne. The high success rate in finding donors over the years at our center (38.1%) led us to examine our database retrospectively in order to evaluate the donor search and haplotype frequencies (HFs) in the sample. Our goal was to identify the factors contributing to this high success rate and also to compare the HFs we observed with other reported haplotype frequency estimations (HFE) for the Cologne area. Probability estimations for a successful donor search were constructed based on the HFEs for the sample.